THE EFFICIENCY OF CHARCOAL AS A FILTER MEDIA IN NON-VEGETATION CONSTRUCTED WETLAND SUBSURFACE-FLOW SYSTEM (SF) FOR AMMONIA, CHEMICAL OXYGEN DEMAND, AND IRON TREATMENT OF LANDFILL LEACHATES - Ahmad Md. Noor; Pedy Artsanti; P.E. Lim; S. Suryani; H.P.S Abdul Khalil (Indonesian Journal of Chemistry, 2003)
The thermal Charcoal for domestic used was crushed into powder and mixed with gravel. Four reactors of different proportion and size of charcoal and gravel were set up without vegetation. Sample of landfill leachates obtained from site of Pulau Burung Landfill, Penang, was introduced into the reactors. Ammonia, chemical oxygen demand (COD), and iron of inlet and outlet from four reactors were analyzed by standard methods. Result shows that overall performance of removing ammonia and iron were much better than COD.